Doing it for the children. Issue 2 (2nd July 2016) - Thomas, Pattie
ABSTRACT: The evidence is mounting that the "Fight Against Childhood Obesity" is bad policy that may do more harm than good for children. Instead of lamenting how we got to the point of hurting kids in the name of helping them, Dr. Thomas proposes policy guidelines to create government and private programs that affect children's health, education, and development. She asserts that by following these principles, unintentional harms could be avoided or, at least, reduced.